EFFECT OF SERVICE QUALITY ON CUSTOMER SATISFACTION Case Study at PT. Asuransi Allianz Life Indonesia - One, Jumirah; Darini, M.Si, Dra. Sri; Septi W, SE., MM, Helly (Management, 2010)
The research thesis under the title Influence on Service Quality Customer Satisfaction. Asuransi Allianz Life Indonesia Marketing Branch Office in Yogyakarta held in August 2008 to October 2008 with respondents Customer. Asuransi Allianz Life Indonesia Yogyakarta Marketing Branch. This thesis research aims to determine whether the effect on Quality of Service Customer Satisfaction PT. Asuransi Allianz Life Indonesia Yogyakarta Marketing Branch. Data collection method used in this study are interviews and questionnaires. While the methods of data analysis used in this research is descriptive analysis method and quantitative measurement method which can be expressed with numbers. Based on the analysis of multiple linear regression equation with t test results can be seen that the variables affect the reliability of Customer Satisfaction with t calculate the size of the t table (2.699> 1.984), Response variables affect customer satisfaction with t calculate the size of the t table (1.996> 1.984 ), the variables affecting Customer Satisfaction Guarantee with t calculate the size of the t table (2.725> 1.984). In calculating the F test results also can be seen that the variable Reliability, Response and Security jointly affect Customer Satisfaction with calculated F value is greater than F table (15.047> 3089). Among the variables tested was variable Assurance has the highest value (dominant) that is equal to 2.725 compared with variable Reliability and Responsiveness in influencing customer satisfaction with the beta coefficient of 0.212 is greater than the reliability of the variables that have a value of 0.204 and Response with a value of 0.121.Customer satisfaction is dominantly influenced by the Guarantee given by PT. Asuransi Allianz Life Indonesia Yogyakarta and Marketing Branch Reliability and Response variable with a value of 0.566 or 56.6% while 43.4% influenced by other variables other non-teramasuk in this study. Keywords: customer satisfaction, quality of service.